The Geomagnetic Kp Index and Derived Indices of Geomagnetic Activity - J. Matzka; C. Stolle; Y. Yamazaki; O. Bronkalla; A. Morschhauser (Space Weather)
Abstract The geomagnetic Kp index is one of the most extensively used indices of geomagnetic activity, both for scientific and operational purposes. This article reviews the properties of the Kp index and provides a reference for users of the Kp index and associated data products as derived and distributed by the GFZ German Research Centre for Geosciences. The near real‐time production of the nowcast Kp index is of particular interest for space weather services and here we describe and evaluate its current setup.